Beyond Reef Restoration: Next-Generation Techniques for Coral Gardening, Landscaping, and Outreach - Schmidt-Roach, Sebastian; Duarte, Carlos M.; Hauser, Charlotte A. E.; Aranda, Manuel (Frontiers in Marine Science, 2020)
Anthropogenic disturbances have led to the degradation of coral reefs systems globally, calling for proactive and progressive local strategies to manage individual ecosystems. Although restoration strategies such as assisted evolution have been recently proposed to enhance the performance of coral reef populations in response to current and future stressors, scalability of these concepts and implementation in habitat or ecosystem-wide management remains a major limitation for logistical and financial reasons. We propose to implement these restoration efforts into an ecotourism approach that embeds land-based coral gardening efforts as architectural landscape elements to enhance and beautify coastal development sites, providing additional values and rationale for ecotourism stakeholders to invest. Our approach extends and complements existing concepts integrating reef restoration in ecotourism projects by creating a participatory platform that can be experienced by the public, while effectively integrating numerous restoration techniques, and providing opportunities for long-term restoration and monitoring studies. In this context, we discuss options for pre-selection of corals and systematic, large-scale monitoring of coral genotypic performances targeting higher resilience to future stressors. To reduce operating costs during out-planting, we suggest to create coral seeding hubs, clusters of closely transplanted conspecifics, to quickly and efficiently restore/enhance active reproduction. We discuss our land-based coral gardening approach in the context of positive impacts beyond reef restoration. By restoring and strengthening resilience of local populations, we believe this strategy will contribute to a net positive conservation impact, create a culture on restoration and enhance and secure blue economical investments that rely on healthy marine systems.